A novel cause for primordial dwarfism revealed: defective tRNA modification. Issue 1 (December 2015) - Filonava, Liudmila; Torres, Adrian; de Pouplana, Lluis
Abstract A mutation in theWDR4 gene, coding for a tRNA-modifying enzyme, leads to reduced levels of guanosine methylation in tRNA in patients with primordial dwarfism. See related Research article:http://www.genomebiology.com/2015/16/1/210 .